THE PROBLEMS OF DA'WAH UMMAH - Zamakhsyari Abdul Majid (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
The article titled "The Problems of Dakwah Ummah" offers an in-depth exploration of the contemporary challenges faced by the Ummah (the global Muslim community) in propagating Islamic teachings and values, known as dakwah. As globalization continues to interconnect societies, new platforms and mediums for dakwah emerge, but so do an array of complications. This piece sheds light on various facets such as the influence of modern technology on dakwah, the potential distortion of religious messages, socio-political constraints, and cultural adaptations. It also underscores the necessity for a holistic understanding and a renewed methodology in dakwah to ensure its efficacy in contemporary contexts. Through a careful balance of historical analysis, and case studies, this article provides both a diagnostic view and prospective solutions for the ongoing struggles of dakwah in the Ummah